Thermal electric cooling system based on Arduino module for diode pumped solid state laser - Johari, Abdul Rahman (2018)
Cooling system is very important in a solid state laser in order to avoid thermal damage on the gain medium and to stabilize the laser output. The cooling system is also important to prevent any unwanted phenomena such as condensation of water which can degrade the performance of laser as well as moisten the gain medium area. The previous laser system used by the local group research do not have automatic cooling system. Problem arises when the temperature went down below dew point temperature and water droplets accumulate in the gain medium crystal. In effort to overcome this drawbacks, a smart cooling system is designed and developed. A diode-pumped solid state (DPSS) laser system consists of ND:YVO4 crystal as a gain medium, a 97% partial reflective mirror to stand as an output coupler and a diode laser at 808 nm wavelength with 3 W maximum output power as a pumping source to produce 1064 nm output laser. The pumping source, gain medium and output coupler were aligned on a heat sink platform to form a linear optical resonator. The gain medium of Nd:YVO4 was placed in a U-shape copper holder. The crystal was properly wrapped with indium to sustain good heat contact. The cooper holder was coupled with a thermoelectric cooler (TEC). A microcontroller was designed with the aid of an Arduino technology. Software was developed to command the microcontroller to set the desired temperature of the gain medium automatically. The output of the DPSS laser was tested by verifying the TEC temperature. The best laser performance was identified at an optimized TEC temperature of 18 °C with maximum power output achieved at 300 mW corresponding to a slope efficiency of 31.20%. A slight increase in slope efficiency of about 2.5% is obtained when an automatic adjustment of the TEC temperature is employed. The implementation of automatic TEC temperature control has been shown to improve the efficiency of laser output power with advantages of it being low cost and ease of assembly.